Jak twórczość mistrza polskiego reportażu stała się „peryferyjną”? O recepcji Jeszcze dzień życia R. Kapuścińskiego w kulturze macedońskiej - Tanuševska, Lidija (Przekłady Literatur Słowiańskich, 2019)
This article is about the reception of Kapuściński’s book Another Day of Life which was translated and published in Macedonia in 2017. This text explains the reasons of the delayed translation of Kapuściński’s book and the social environment surrounding its reception, as well as the reception of the reportage as a literary genre in Macedonia. Those are part of the reasons why this literary master has passed by almost unnoticed in this culture and his works are pushed aside from the main literary streams. The article also deals with translating problems concerning the alienation / otherness and the way foreign realities are transferred from Polish to Macedonian language.